The role of single nucleotide polymorphisms and copy number variations in the spectrum of non-alcoholic fatty liver disease / Shamsul bin Mohd Zain - Mohd Zain, Shamsul (2013)
Non-alcoholic fatty liver disease (NAFLD) has been recognised as a growing public health problem worldwide. NAFLD is a spectrum ranging from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. Simple steatosis is generally benign condition whereas NASH can potentially progress to serious liver complications, including liver cancer. Genetic factors have been shown to play a significant role in the pathogenesis of NAFLD and may be responsible for the different phenotypes among individuals, including predisposition to severe liver disease. Genomic variability may present in various forms such as single nucleotide polymorphisms (SNPs), structural alterations (deletion, duplication and inversion), variable number of tandem repeats (VNTRs) and presence or absence of transportable element. Of all these variations, the commonest is the SNP. Copy number variation (CNV) is another type of mutation that could serve as a genetic marker for the NAFLD spectrum, and to date, there is no published report on CNV in NAFLD. This study aimed to investigate the association between SNPs of candidate genes with susceptibilty to NAFLD and the severity of the underlying liver disease. This study further identified genomic amplifications and deletions (CNVs) in the spectrum of NAFLD. A total of 144 biopsy-proven NAFLD patients and 198 controls without NAFLD were genotyped for polymorphisms of various candidate genes. Whole-genome array comparative genomic hybridization (aCGH) method was used to detect CNVs in a total of 40 patients with NASH and 40 age, gender, and ethnicity-matched controls. The polymorphisms of PNPLA3, LEPR¸ and GCKR render susceptibility to NAFLD (OR 2.23, 95% CI 1.60-3.11, P < 0.0001; OR 1.64, 95% CI 1.18-2.28, P = 0.003; and OR 1.49, 95% CI 1.09-2.05, P = 0.012, respectively) while SNPs of AGTR1 render protection against the condition (OR 0.40, 95% CI 0.20-0.81, P = 0.01). The G allele of both the PNPLA3 rs738409 and the AGTR1 rs3772622 were associated with increased fibrosis score (P < 0.05). For LEPR rs1137100, the G allele was associated with lower fibrosis score (P < 0.05). Analysis of gene-gene interaction revealed a strong interaction between the AGTR1, LEPR and GCKR genes with the PNPLA3 gene (empirical P = 0.007, empirical P = 0.001 and empirical P = 0.003, respectively). Genome wide profiling identified five most frequently amplified CNVs located on the chromosome 14q11.2 (62.5%), 12p13.31 (50.0%), 11p15.4 (45.0%), 5p15.33 (42.5%), and 12p13.2 (40.0%). The most frequently deleted CNVs were located on chromosome 11q11 (35.0%), 12p13.2 (32.5%), 16q12.2 (32.5%), 4q13.2 (32.5%), 1q21.3 (32.5%), and 14q24.3 (32.5%). It can be hypothesised that these CNVs may be implicated in mechanisms that lead to progression to NASH. Of particular note was a 0.02 Mb deletion on chromosome 16q12.2. This region is rich in carboxylesterase 1 gene (CES1) that is important in cholesterol transportation leading to fatty liver. Downstream studies to validate findings are being pursued. Overall, this study showed the complex nature of NAFLD involving multiple gene interactions. The copy number findings are novel and could serve as potential genetic marker for the identification of the potentially progressive form of NAFLD.